Scaling Framework for goats in Borana, Konso, South Omo and Jinka clusters - Belay, Berhanu; Getachew, Tesfaye; Haile, Aynalem (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
Goats in the lowlands of Ethiopia (South Omo, Borena, and Konso) provide economic and livelihood options for pastoralists and Agro-pastoralists. They are also the main sources of live goat and slaughter meat exports. The Community-Based Breeding Program, an alternative genetic improvement approach, intends to improve the indigenous goat breeds by participating the community and capturing indigenous knowledge. Community-based breeding program has been piloted in the lowlands and highlands of Ethiopia, which need to be scaled up. A consultative workshop was conducted to demonstrate the scaling framework to expand the activity of CBBP at the breed level through clustering. The consultative workshop followed an opening speech, background paper presentation, group discussion, and cluster formation and setting the steering committee of the cluster for goat improvement. The discussions, followed by background paper presentation, group discussion, and reflections, and the concluding remarks of the workshop showed an opportunity to improve the indigenous goats for domestic consumption and export. The vast population and genetic diversity are opportunities to enhance indigenous goats. The goat cluster initiative is named BOOM goat improvement initiative through the engagement of the key stakeholders. The BOOM goat inititative is divided into 3 sub-cluster namely S.Omo -Ari, Borena and Jinka targeting to breed with proven sires to 1,293,883, 235,670 and 130, 653 does, respectively. The initiative is steered by seven steering committee members drawn from different offices/stakeholders. The steering committee shall mobilize resources, coordinate stakeholders in goat CBBP activities, organize the community into breeder cooperatives, and improve goats.